EPID-11. NATIONAL EPIDEMIOLOGY AND SURVIVAL OF ADULT-TYPE DIFFUSE GLIOMAS IN THE UNITED STATES BY IDH, 1P/19Q, MGMT, AND WHO CNS GRADE. (14th November 2022) - Iorgulescu, Bryan; Sun, Chuxuan; Cioffi, Gino; Neff, Corey; Shoaf, Madison; Waite, Kristin; Kruchko, Carol; Wen, Patrick Y; Brat, Daniel; Ostrom, Quinn; Barnholtz-Sloan, Jill
Abstract: BACKGROUND: Histomolecularly-defined adult-type diffuse gliomas—including IDH-wildtype glioblastoma, IDH-mutant astrocytoma, and IDH-mutant 1p/19q-codeleted oligodendroglioma—were incorporated into U.S. cancer registry reporting for individuals with brain tumors beginning in 2018. We therefore assessed their epidemiology and overall survival (OS) patterns. METHODS: Individuals histopathologically diagnosed with diffuse gliomas in 2018 and had brain molecular marker data were identified within the National Cancer Database; Surveillance, Epidemiology, and End Results Incidence; and Central Brain Tumor Registry of the United States databases. Age-adjusted incidence rates per 100, 000 population with 95% confidence intervals (95CI) were estimated. OS was estimated using Kaplan Meier methods and stratified by WHO CNS grade, age, sex, tumor size, treatment, extent of resection, and MGMT promoter methylation. WHO CNS grade was additionally examined among individuals with IDH-wildtype diffuse astrocytic gliomas. RESULTS: IDH-wildtype glioblastomas' incidence rate was 1.74 (95CI = 1.69-1.78); as compared to 0.14 (95CI = 0.12-0.15), 0.15 (95CI = 0.14-0.16), and 0.07 (95CI: 0.06-0.08) WHO grade 2, 3, and 4 IDH-mutant astrocytomas. Irrespective of grade, IDH mutation prevalence was highest in adolescents & young adults, and IDH-mutant astrocytomas were more frequently MGMT promoter methylated. For OS analysis, 8, 651 individuals were identified: one-year OS was 53.7% for WHO grade 4 IDH-wildtype glioblastomas (95CI = 52.5-54.9); 98.0% (95CI = 96.1-99.0), 92.4% (95CI = 89.6-94.5), and 76.3% (95CI = 70.1-81.3) for grade 2, 3, and 4 IDH-mutant astrocytomas; 97.9% (95CI = 95.9-98.9) and 94.4% (95CI = 90.9-96.6) for grade 2 and 3 IDH-mutant 1p/19q-codeleted oligodendrogliomas. Among IDH-wildtype glioblastomas, median OS was 17.1 months (95CI = 16.1-18.6) and 12.4 months (95CI = 12.0-12.9) for methylated and unmethylated MGMT promoters. IDH-wildtype diffuse astrocytic gliomas reported as WHO grade 2 or 3 demonstrated longer adjusted OS compared to grade 4 tumors (both p < 0.001). A significant association was not observed between chemotherapy and OS (HRadjusted 0.95, 95CI = 0.41-2.22, p = 0.91) for radiotherapy-treated grade 3 IDH-wildtype diffuse astrocytic gliomas. CONCLUSIONS: Our findings provide the initial U.S. epidemiological estimates for histomolecularly-defined adult-type diffuse gliomas.